Influence of an interface layer on the effective coupling at a ferromagnet/antiferromagnet interface - Chew, Khian Hooi; Stamps, R.L. (2010)
We examine the exchange anisotropy induced at a ferromagnetic/antiferromagnetic interface when an antiferromagnetic interface layer exists. We show that competition between exchange couplings in the interface layer can result in a ferrimagnetic-like compensation point. This leads to a reversal of the effective field acting on the ferromagnet, and a consequent sign change of the exchange bias for temperatures near the Neel temperature of the antiferromagnet. A surprising result is the sensitive dependence of the compensation point on exchange interactions. Even minute modifications of the exchange interactions near the interface can result in a reversal of the effective field, provided certain conditions are met. (C) 2009 Elsevier B.V. All rights reserved.